2023
DOI: 10.1021/acsomega.2c06497
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Fracture Network Expansion Mechanism and Three-Dimensional Reconstruction Characteristic of High-Rank Coal in Guizhou Province, China

Abstract: To better understand the fracture propagation characteristics and spatial distribution pattern of a high-rank coal reservoir during hydraulic fracturing, a true triaxial physical simulation device was used to conduct a hydraulic fracturing experiment on large-sized raw coal from Zhijin, Guizhou Province, China. Computed tomography technology was used to scan the three-dimensional morphology of the fracture network before and after fracturing, then AVIZO software was used to reconstruct the internal fractures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…In addition, permeability stands as the pivotal determinant influencing the extraction of coal-measured gas within reservoirs. The intricate geological characteristics inherent in deep coal measure reservoirs lead to notably diminished coal permeability. , Numerous fracturing tests regrading sandstone, shale, and coal mass have demonstrated that creating complex cracks is critical to enhance the overall permeability of reservoirs. A large number of studies have confirmed the effects of supercritical carbon dioxide (ScCO 2 ) on pore and fracture structures at different scales, confirming that its unique physical and chemical properties enable it to enhance the permeability of coal. , Noteworthy contributions to this field include comparative analysis of shale permeability (φ25 × 50 mm) following ScCO 2 fracturing versus hydraulic fracturing under the same stress conditions . The results show that ScCO 2 -induced fracturing increases the shale permeability by up to three times compared to hydraulic fracturing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, permeability stands as the pivotal determinant influencing the extraction of coal-measured gas within reservoirs. The intricate geological characteristics inherent in deep coal measure reservoirs lead to notably diminished coal permeability. , Numerous fracturing tests regrading sandstone, shale, and coal mass have demonstrated that creating complex cracks is critical to enhance the overall permeability of reservoirs. A large number of studies have confirmed the effects of supercritical carbon dioxide (ScCO 2 ) on pore and fracture structures at different scales, confirming that its unique physical and chemical properties enable it to enhance the permeability of coal. , Noteworthy contributions to this field include comparative analysis of shale permeability (φ25 × 50 mm) following ScCO 2 fracturing versus hydraulic fracturing under the same stress conditions . The results show that ScCO 2 -induced fracturing increases the shale permeability by up to three times compared to hydraulic fracturing.…”
Section: Introductionmentioning
confidence: 99%